Preparing effective tables - Ng, K.H.; Peh, W.C. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Tables are used in scientific papers to present information in a concise and efficient manner. Tables are able to provide information at any desired level of detail and precision. Presenting data in a table rather than as part of the text is also an effective way to reduce the length of the text. This article provides some basic guidelines to assist authors in preparing clear and effective tables for their papers.